2010
DOI: 10.1007/s11434-009-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of arsenic in soils by stabilized nanoscale zero-valent iron, iron sulfide (FeS), and magnetite (Fe3O4) particles

Abstract: Arsenic is a widespread contaminant in soils and groundwater. While various iron-based materials have been studied for immobilizing arsenic in contaminated soils, the feasibility of stabilized iron-based nanoparticles has not been reported. This study investigates the effectiveness of using three types of starch-stabilized iron-based nanoparticles, including zero-valent iron (ZVI), iron sulfide (FeS), and magnetite (Fe 3 O 4 ), for immobilization of arsenic in two representative As-contaminated soils (an orcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(23 citation statements)
references
References 48 publications
(60 reference statements)
0
22
0
1
Order By: Relevance
“…Among various stabilizers tested, starch has been recognized as an effective, low-cost and environmentally benign material. Starch-stabilized magnetite nanoparticles (SMNP) have displayed much improved physical stability, soil mobility, and sorption capacity for arsenic compared with non-stabilized bare magnetite particles (He and Zhao, 2005;Zhang et al, 2010;An et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among various stabilizers tested, starch has been recognized as an effective, low-cost and environmentally benign material. Starch-stabilized magnetite nanoparticles (SMNP) have displayed much improved physical stability, soil mobility, and sorption capacity for arsenic compared with non-stabilized bare magnetite particles (He and Zhao, 2005;Zhang et al, 2010;An et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In last decade, ZVINs have been investigated as a new tool for the treatment of contaminated water and soil [8][9][10][11][12][13]. The ZVINs applications as a solution for some problems caused by pollutants are being used successfully for treating the various heavy metal ions including Cr 6?…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the use of ZVINs to remediate As-polluted soils is a promising in situ strategy [30]. Zhang et al [13] reported a high reduction of As bioavailability in soils after treatment with ZVINs. Alidokht et al [31] also found good results for Cr immobilization in a spiked soil following the starch-stabilized ZVINs application.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a two-dimensional nanomaterial that has between one and ten layers of sp 2 -hybridized carbon atoms arranged in six-membered rings. It has many unique properties, including interesting transport phenomena, and high Young's modulus (approximately 1100 GPa) [ Importantly, it could be used in pollutant removal in environmental remediation, which has attracted increasing research in recent few years [5][6][7][8][9][10] and is the focus of this review. Aggregation of graphene layers determines the practical specific surface area, and modification of pristine graphene with other compounds will decrease the aggregation and increase the effective surface area.…”
mentioning
confidence: 99%